Epidemiological characteristics of premature infants born at General Hospital Pula in a five-year-period (2012-2016) : Epidemiološke karakteristike nedonoščadi rođene u Općoj bolnici Pula u petogodišnjem razdoblju (2012.-2016.) - Jašić, Mladen (Array, 2021)
Aim: To summarize our five-year experience in management of premature infants at our second level neonatal facility. Patients and methods: This prospective birth cohort study was performed at the Division of Neonatology (level 2), Department of Paediatrics, General hospital Pula during a five-year-period (January 1st 2012 – December 31st 2016). The study population included all live-born neonates born between 22nd and 37th gestational week. Results: During the above mentioned five-year-period, 289 premature infants were born at General Hospital Pula. One-hundred and sixty seven (58%) neonates were delivered vaginally and 122 (42%) were delivered by caesarean section. Nineteen (7%) neonates were born after in vitro fertilization. Infants were mostly male (N=167; 58%), and appropriate for gestational age (N=240; 83%). Also, the infants belonged mostly to the late-preterm group (N=245; 85%). Thirty-three premature infants (11%) were transferred to a tertiary paediatric centre and five neonates died (2%). The overall cost of hospital stay for hospitalized premature infants was 2,517,000 Croatian kunas (cost for one patient: median 4800, range 3,225-53,325); in euros, it was 335,600 (cost for one patient: median 640, range 430-7,110) respectively. The overall hospital stay was 10.01±8.30 days (median 8.00, range 1.00-67.00). Conclusion: Despite the great development of neonatal intensive care, the best prevention of complications related to prematurity is to prevent preterm labour.